Utility of DNA Profiling From Main Pancreatic Duct Fluid by Endoscopic Ultrasound and Endoscopic Retrograde Cholangiopancreatography to Screen for Malignant Potential. Issue 5 (May 2020) - Simpson, Rachel E.; Flick, Katelyn F.; Gromski, Mark A.; Al-Haddad, Mohammad A.; Easler, Jeffrey J.; Sherman, Stuart; Fogel, Evan L.; Schmidt, C. Max; DeWitt, John M.
Abstract : Objectives: The yield of genetic testing of main pancreatic duct (MPD) fluid collected during endoscopic retrograde cholangiopancreatography (ERCP) versus endoscopic ultrasound-guided fine-needle aspiration is unclear. Methods: Consecutive MPD fluid samples obtained by endoscopic ultrasound/ERCP with DNA profiling were reviewed, excluding specimens designated "no amplification." Invasive disease included invasive cancer or malignant cytology. Results: One hundred ten samples from 109 patients who underwent ERCP (n = 32) or endoscopic ultrasound-guided fine-needle aspiration (n = 78) were analyzed (2007–2018). Leading indications were dilated MPD and suspected intraductal papillary mucinous neoplasm. Elevated DNA quantity, KRAS, loss of heterozygosity (LOH), and GNAS mutations occurred in 61.5%, 25.5%, 16.4%, and 8.7% of samples, respectively. Elevated DNA quantity occurred more frequently in ERCP samples (84.4% vs 51.9%, P = 0.002); other mutation yields were similar ( P > 0.05). Invasive pathology ( P = 0.032) was associated with LOH in the subset of patients who underwent surgery (n = 44). Adverse events occurred more frequently after ERCP (28.1% vs 9.0%, P = 0.016). Conclusions: Endoscopic MPD fluid sampling may yield genetic data to improve diagnosis and risk stratification. In our surgical cohort, LOH was the sole predictor of invasive pathology. Endoscopic ultrasound-guided fine-needle aspiration of MPD fluid, when possible, is preferred because of superior safety profile.